Genes involved in muscle contractility and nutrient signaling pathways within celiac disease risk loci show differential mRNA expression - Montén, Caroline (BMC Med Genet, 2015)
BACKGROUND: Risk gene variants for celiac disease, identified in genome-wide linkage and association studies, might influence molecular pathways important for disease development. The aim was to examine expression levels of potential risk genes close to these variants in the small intestine and peripheral blood and also to test if the non-coding variants affect nearby gene expression levels in children with celiac disease. METHODS: Intestinal biopsy and peripheral blood RNA was isolated from 167 children with celiac disease, 61 with potential celiac disease and 174 disease controls. Transcript levels for 88 target genes, selected from celiac disease risk loci, were analyzed in biopsies of a smaller sample subset by qPCR. Differentially expressed genes (3 from the pilot and 8 previously identified) were further validated in the larger sample collection (n = 402) of both tissues and correlated to nearby celiac disease risk variants. RESULTS: All genes were significantly down- or up-regulated in the intestinal mucosa of celiac disease children, NTS being most down-regulated (Fold change 3.6, p < 0.001). In contrast, PPP1R12B isoform C was up-regulated in the celiac disease mucosa (Fold change 1.9, p < 0.001). Allele specific expression of GLS (rs6741418, p = 0.009), INSR (rs7254060, p = 0.003) and NCALD (rs652008, p = 0.005) was also detected in the biopsies. Two genes (APPL2 and NCALD) were differentially expressed in peripheral blood but no allele specific expression was observed in this tissue. CONCLUSION: The differential expression of NTS and PPP1R12B indicate a potential role for smooth muscle contractility and cell proliferation in celiac disease, whereas other genes like GLS, NCALD and INSR suggests involvement of nutrient signaling and energy homeostasis in celiac disease pathogenesis. A disturbance in any of these pathways might contribute to development of childhood celiac disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12881-015-0190-1) contains supplementary material, which is available to authorized users.